Structural Design and Technology of Pocket Foundations for Long Precast Concrete Columns in Seismic Areas - Horia Constantinescu; Traian-Nicu Toader (Buildings)
The connection between a prefabricated reinforced concrete column and a pocket foundation is a case treated from a general perspective in the European Standard named EN 1992-1-1 (EC2), and when the structural engineer deals with the dimensioning or verification of the connection, he must tackle several unknowns. The present work aims to fill in the missing information by presenting detailed calculation models based on the strut-and-tie method for four widely used pocket foundations: a pedestal pocket foundation with smooth, rough or keyed internal walls and a pad foundation with a pocket possessing keyed internal walls. In establishing the strut-and-tie models and writing the equation for the internal forces, we consider several standards (EC2, NBR 9062 and DIN 1045-1), good practices (from Austria, England, Germany and Romania) and numerous experimental and numerical investigations. Additionally, detailed design prescriptions applicable to seismic areas are given. This manuscript covers a wide range of design and technology aspects necessary for designing and building columns connected with pocket foundations, information for which is shown only in fragmented form or partially in other publications. Afterward, as a case study, a pocket foundation is designed in all four variations, with the structural design particularities, similitudes and differences being pointed out. Finally, to conclude, we mention the advantages and disadvantages of pocket foundations with respect to the type of internal wall surface used. Quantifiable data based on the case study undertaken are available.